A base de conhecimento para o ensino de sólidos arquimedianos - Almeida, Talita Carvalho Silva de (2015)
This research aims to identify the teaching knowledge mobilized for Archimedean solids are taught. Thus, the research question was: which knowledge base for the Archimedean solid education in basic school? To answer this question we resort to a bibliographical study developed based on material already prepared, consisting of books and scientific articles. The theoretical framework was based on Mathematical Knowledge for Teaching, in sense Ball, Thames and Phelps, and Technological Knowledge for Education, in sense Mishra and Koehler, both obtained with advances in the initial proposal of Shulman and colleagues about the knowledge base for teaching and the Anthropological Theory of Didactic Yves Chevallard. Such references were fundamental in the composition of a scene that showed that teaching knowledge are minimally involved in the Archimedean solids teaching process. The methodological choice for the literature contributed to the achievement of the desired goal, since it allowed us to find aspects of knowledge not evidenced in studies by Shulman. The choice of a mathematical procedure performed by Renaissance as Mathematics Reference Model Epistemological led us to an Mathematics Organization and a possible Didactic Organization for Archimedean solids helping us to realize that the teaching knowledge come from the interaction of three particular components of knowledge, mathematical knowledge, technological knowledge and didactic knowledge